The temporal and geographical distribution and diversity of disease-associated Neisseria meningitidis genetic types in Europe - Brehony, C (2010)
Meningococcal disease, caused by the bacterium Neisseria meningitidis, is an important cause of morbidity and mortality in young children and adolescents worldwide. There are 12 serogroups with most disease due to meningococci expressing one of five capsular polysaccharide antigens corresponding to serogroups A, B, C, Y and W135. In Europe, the majority of disease-causing strains are of serogroups B and C. No comprehensive vaccine is available against the bacterium due to the difficulty in producing serogroup B vaccines. A number of countries, e.g. UK and the Republic of Ireland have implemented routine meningococcal conjugate C (MCC) vaccine strategies. Due to the high proportion of disease accounted for by serogroup B in Europe and other developed countries, much research is currently being carried out to unearth vaccine candidates that would be protective and give as wide coverage as possible. Such candidates include the antigens PorA, FetA and factor H-binding protein. Potential drawbacks with antigens such as these which are under immune selection are high degrees of variability and lack of cross-immunity. Determination of the distribution, both geographically and temporally, of antigens and their association with clonal complex can aid in the formulation of novel vaccines and assess their potential coverage across Europe. Serological typing schemes involving characterisation of the polysaccharide capsule (serogroup) and outer membrane proteins such as PorA (serosubtype) and PorB (serotype) have been used for a number of years with some success. However, drawbacks associated with these methods include insufficient discrimination, limitations in panels of monoclonal antibodies used in the typing procedures and difficulty in comparison of results among labs. Consequently, in recent years genotypic methods such as multi-locus enzyme electrophoresis (MLEE) and subsequently multi-locus sequence typing (MLST) have been developed. These methods measure the variation in slowly evolving housekeeping genes whereas serological methods measure variation in antigens which are under immune pressure and are therefore more diverse. Combination of phenotypic and genotypic typing methods can offer high levels of discrimination. Molecular studies into meningococcal diversity have offered many important insights into its population biology, which have implications for prevention and control of meningococcal disease. These have included the identification of hyperinvasive lineages and the correlation of genetic type with antigenic type and disease epidemiology. The EU-MenNet programme was established as a pan-European infrastructure for the research and surveillance of European meningococcal disease. Its aim was to coordinate and disseminate the latest molecular isolate characterisation techniques (MLST) and electronic data transfer via the Internet to exploit epidemiological and population genetic studies. Within the EU-MenNet, the European Meningococcal MLST Centre (EMMC) was set up to carry out molecular typing — MLST, PorA and FetA — of European disease isolates from 18 countries over three years 2000, 2001 and 2002. The output of this project will be the largest representative molecular epidemiological study of meningococcal disease in Europe. Assessment of the data produced will give insights into the geographic and temporal distribution and structuring of disease-associated clonal complexes and antigens and their associations. This will give an indication of the meningococcal disease population in Europe and will be invaluable for the current, and ongoing, development and introduction of new meningococcal vaccines.